Trinity Church (Alserkirche) in Vienna-Alsergrung - Czoernig-Gobanz, Herta, 1886-1970 (artist):::Creator:::::::::::: (2020)
Hand-colored etching of the Trinity Church (Dreifaltigkeitskirche der Minoriten) in Vienna, estate signed, with musical incipit for the second movement (funeral march) from Beethoven's Eroica Symphony.